Comparison of recruitment patterns during on-water and on-ergometer rowing - Fleming, N.; Donne, B. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The development of dynamic rowing ergometers which more accurately simulate on-water biomechanics have led to their increased use in training. While electromyographic (EMG) and kinematic analysis of rowing ergometer designs has been performed (Nowicky et al., 2005); a direct comparison to the on-water scenario is necessary. This study assessed recruitment patterns during onergometer and on-water rowing to validate task specificity of rowing ergometry. Methods: Male rowers (n=10; age 21±2 yr, height 1.90±0.05 m, body mass 83.3±4.8 kg) performed 3 by 3 min exercise bouts at heart and stroke rates equivalent to 75, 85 and 95% VO2max on both dynamic and stationary rowing ergometers and on-water. During exercise, surface EMG data were recorded (Mega ME6000) from Rectus Femoris (RF), Vastus Medialis (VM), Biceps Femoris (BF) and Erector Spinae (ES). Video recording at 50 Hz with audio triggers pre- and post-exercise facilitated data synchronisation. EMG data from 10 consecutive stroke cycles in the latter stage of each bout were amplitude processed via root mean squaring and normalised relative to pre-trial maximal sprints. Overall muscle activity within cycle was quantified via integration (iEMG) of rmsEMG data. Mean data for 10% interval of stroke cycle were compared using repeated measures ANOVA, Tukey post-hoc tests quantified significant differences (P<0.05). Results: iEMG activity significantly increased in RF (75 vs. 95%; 118±17 vs. 130±20 ìv.s, P<0.01) and VM (75 vs. 95%; 195±28 vs. 249±29 ìv.s, P<0.01) as exercise intensity increased. No intensity related differences were observed in BF or ES. Comparing rmsEMG data across rowing conditions revealed significant differences at discrete 10% intervals of stroke cycle in RF and VM. On-water RF activity was significantly greater than dynamic ergometry at the 10 and 20% interval (P<0.01). On-water RF activity was also significantly greater than both rowing ergometer conditions at 60 (P<0.01) and 70% (P<0.001) intervals. During the drive phase (10, 20 and 30%) mean VM activity was significantly greater on-water vs. on-ergometer; these differences were most pronounced at 95% VO2max. While on-water ES activity at the 20% interval was significantly greater than on-ergometer (P<0.05) during exercise at 75% VO2max, significant differences were not observed at 85 and 95% VO2max. No significant differences in BF activity were observed across condition at any exercise intensity. Discussion: Results suggest that significant difference exist comparing recruitment patterns during on-water and on-ergometer rowing. These differences may be due to altered acceleration and deceleration of moving masses on-ergometer which do not perfectly simulate the on-water scenario.